Height-velocity diagram analysis of a variable speed rotor helicopter - Yan, X.; Chi, C.; Chen, R. (My University, 2018)
This paper applies optimal control method to study the effects of variable speed rotor (VSR) on the helicopter Height-Velocity (H-V) diagram in one engine inoperative (OEI) situation. Taken UH-60A as a sample helicopter, a flight dynamics model and the optimal control method applied are validated against the flight test data. The low-speed H-V diagram in OEI and the landing procedures at three key points (High hover, Knee and Low hover points) of the H-V diagram in OEI are investigated under different rotor operating speeds. Results indicate that the reduction of rotor operating rotation speed will cause the area of H-V diagram in OEI gradually shrink at first, and then expand rapidly. The rotor operating speed corresponding to the minimum area of H-V diagram in OEI is a little higher than that corresponding to the minimum required power. A reasonable rotor operating rotation speed not only effectively reduces the helicopter required power, but also improves the landing performance in OEI.